Quadruped Robots: Bridging Mechanical Design, Control, and Applications - Qimeng Li; Franco Cicirelli; Andrea Vinci; Antonio Guerrieri; Wen Qi; Giancarlo Fortino (Robotics)
Quadruped robots have emerged as a prominent field of research due to their exceptional mobility and adaptability in complex terrains. This paper presents an overview of quadruped robots, encompassing their design principles, control mechanisms, perception systems, and applications across various industries. We review the historical evolution and technological milestones that have shaped quadruped robotics. To understand their impact on performance and functionality, key aspects of mechanical design are analyzed, including leg configurations, actuation systems, and material selection. Control strategies for locomotion, balance, and navigation are all examined, highlighting the integration of artificial intelligence and machine learning to enhance adaptability and autonomy. This review also explores perception and sensing technologies that enable environmental interaction and decision-making capabilities. Furthermore, we systematically examine the diverse applications of quadruped robots in sectors including the military, search and rescue, industrial inspection, agriculture, and entertainment. Finally, we address challenges and limitations, including technical hurdles, ethical considerations, and regulatory issues, and propose future research directions to advance the field. By structuring this review as a systematic study, we ensure clarity and a comprehensive understanding of the domain, making it a valuable resource for researchers and engineers in quadruped robotics.